Design And Implementation Of Administration Participation Tender In PT Kencana Alam Putra - Tutut Wurijanto; Lilis Binawati; Ryan Hadi Wijaya (Jurnal Sistem Informasi Universitas Dinamika, 2018)
PT Kencana Alam Putra is a company engaged in contractors who follow the tender of several organizers. The administration process of tender participation encounters some obstacles from checking the tender’s news to the completion of prerequisite documents, such as the recording and providing tender’s information which still uses manual processes, overdue to get the approval from the president director and manager for tender, miss communication and misunderstandings among tender; that makes the preparation for tender take a long time. Based on the description of the issues, a web-based tender administration application was established, which can assist the managing director and manager to get the tender’s news easier.This application can provide notifications to the president director, managers and workers, by providing history or old information that will record the changes from the tender activities. Based on the results of the trial, the web-based tender administrations application can make a list of tender completeness documents required in the process of participating in tender, short message notification for the director and manager in tender approval and short message notification for the workers in field.